Individual and structural influences on the entrepreneurial activities of academics - Teita Bijedić; Frank Maaß; Christian Schröder; Arndt Werner (Institut für Mittelstandsforschung (IfM) Bonn, 2016)
In this paper we study how and to what extend (i) individual working conditions (e.g. peers, working atmosphere, work contract incentives, wage satisfaction), (ii) institutions (e.g. technology transfer offices, patent exploitation agencies, chair in entrepreneurship or awards for academic entrepreneurship) and (iii) network relationships simultaneously affect the likelihood of engaging in entrepreneurial activities (nascent entrepreneurship) in academia. Using unique data collected from 5.992 academic scientists in 73 German Universities Germany, we find that entrepreneurial peers and performance based monetary incentives have a strong positive effect on the entrepreneurial intentions. We show that, although there is a comprehensive support infrastructure for start-ups in German academic institutions, these services are little known amongst their staff. Finally we find that market related networks show a high correspondence with high entrepreneurial intentions, whereas networks within the own university do not have any impact. Several mentioned aspects were analyzed before, but mostly on a limited sample (e.g. only stem field), isolated personal variables (e.g. gender) or isolated environmental aspects (e.g. peer groups). Our study provides a holistic view on the impact of several university-specific structural factors on entrepreneurial intentions among academic scientists in Germany by simultaneously focusing on personal and occupational characteristics for different faculties. – – Wissenschaftliches Hochschulpersonal generiert im Rahmen seiner Forschungstätigkeit Innovationen und verfügt über aktuelles Wissen, das als Basis für eine innovative Unternehmensgründung betrachtet werden kann. Bisher fehlte jedoch eine umfassende empirische Analyse, inwieweit die bestehenden institutionellen Rahmenbedingungen die Gründungsneigung von Wissenschaftlern beeinflussen. Hier setzt die vorliegende Studie an, indem sie die Wirkung personenbezogener und institutioneller Einflussfaktoren (wie Arbeitsbedingungen, Netzwerkbeziehungen und gründungsfördernde Hochschulangebote) untersucht und potenzielle institutionelle Handlungsfelder identifiziert. Die Befragung von 5.992 Wissenschaftlern an 73 deutschen Hochschulen hat gezeigt, dass insbesondere monetäre Anreize im Forschungskontext aber auch Rollenvorbilder im kollegialen Umfeld, Netzwerke - hier insbesondere außerhalb der eigenen Institution - und spezifische Infrastrukturangebote gründungsfördernd wirken.
Keywords: O32; M13; J24; 330; Academic Entrepreneurship; Nascent Entrepreneurship; German Universities; Institutions; Working Conditions; Knowledge Transfer